2021
DOI: 10.1371/journal.pone.0257371
|View full text |Cite
|
Sign up to set email alerts
|

Deep generative models for automated muscle segmentation in computed tomography scanning

Abstract: Accurate gluteus medius (GMd) volume evaluation may aid in the analysis of muscular atrophy states and help gain an improved understanding of patient recovery via rehabilitation. However, the segmentation of muscle regions in GMd images for cubic muscle volume assessment is time-consuming and labor-intensive. This study automated GMd-region segmentation from the computed tomography (CT) images of patients diagnosed with hip osteoarthritis using deep learning and evaluated the segmentation accuracy. To this end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…A joint loading device developed using an iterative design process, has been deemed to have favorable impacts in the realm of efforts to develop a personalized joint loading predictive device. Using this along with imaging, improved network performance, and cartilage cellular and muscle structural and functional measures may add considerably to its clinical utility [30][31][32][33].…”
Section: Additional Observations and Clinical Implicationsmentioning
confidence: 99%
“…A joint loading device developed using an iterative design process, has been deemed to have favorable impacts in the realm of efforts to develop a personalized joint loading predictive device. Using this along with imaging, improved network performance, and cartilage cellular and muscle structural and functional measures may add considerably to its clinical utility [30][31][32][33].…”
Section: Additional Observations and Clinical Implicationsmentioning
confidence: 99%
“…Robotic surgery, computer aided diagnosis, targeted radiation therapy require meticulous segmentation of affected organ from adjacent organs [1][2][3][4][5]. The authors of [6] examined the evolution of automatic multi-organ segmentation techniques, comparing traditional methods with deep learning approaches and found that deep learning methods consistently outperformed traditional approaches, indicating their superior efficiency in segmentation tasks.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, artificial intelligence (AI) approaches, such as deep learning (DL) have become increasingly popular methods for solving various automated computer vision tasks, such as the abovementioned segmentation. The advantage of DL algorithms is their ability to "learn" complex relationships from large datasets in a self-taught way, with minimal operator-imposed assumptions and without explicit knowledge of the data in terms of features to identify objects [4,[19][20][21]. Prior to the recent advances in DL solutions, intensity-based approaches were a common choice; however, they have limitations due to the strong influence of imaging artifacts and variations in the intensity of different organs, which leads to inconsistent and misleading interpretations of the results [22].…”
Section: Introductionmentioning
confidence: 99%